Environmental Impacts of Agricultural Research: Concepts and tools to strengthen evidence base, Brief Number 38 - CGIAR Standing Panel on Impact Assessment (CGIAR Standing Panel on Impact Assessment, 2012)
This brief is based on the paper by Mitch Renkow (2011) Assessing the environmental impacts of CGIAR research: toward an analytical framework. In: CGIAR Independent Science and Partnership Council (2011). Measuring the Environmental Impacts of Agricultural Research: Theory and Applications to CGIAR Research.